Faktor Yang Mempengaruhi Corporate Cash Holding Pada Perusahaan Sektor Industri Barang Konsumsi (Jurnal Paradigma Akuntansi, 2022)
This thesis was prepared with the aim of testing empirically the effect of firm size,leverage, growth opportunity and profitability on corporate cash holding in consumer goodsindustry sector companies listed on the Indonesia Stock Exchange for the period 2017-2019.This study used 79 samples that had been selected according to the purposive samplingmethod. The data processing technique uses multiple linear regression analysis using theMicrosoft Excel program and the IMB SPSS Statistics 25 program. The results obtained inthis test show that firm size has a positive and significant effect on corporate cash holding,leverage has a negative and significant effect on corporate cash. holding, growth opportunitydoes not have a significant effect on corporate cash holding and profitability does not have asignificant effect on corporate cash holding. The implication of this research is that there is arelationship between firm size and leverage on the level of decision making to retain theamount of cash in a company.